Methanol-to-electricity via low-temperature steam reforming integrated with a high-temperature PEM fuel cell - Rehman, Muhammad; Schwarz, Christian; Souzani, Sina; Heßke, Christian; Haumann, Marco (Sustainable Energy & Fuels, 2025)
Liquid organic hydrogen carriers (LOHCs) are a promising method for renewable, green hydrogen transportation from the point of generation using renewable energy to the point of demand. Methanol is one such LOHC with advantages such as high hydrogen content, easy transportation and a simple reaction to release the hydrogen. Herein, we reported the use of a novel supported liquid phase (SLP) catalyst in a miniplant to carry out low-temperature methanol steam reforming (MSR) to release hydrogen and subsequently produce electricity using a high-temperature proton exchange membrane fuel cell (HT-PEMFC). This reformed methanol fuel cell (RMFC) setup successfully ran over the course of 45 h experiencing little catalyst deactivation, producing up to 49.2 lN h−1 of hydrogen and up to 39 W electrical power using HT-PEMFC. Comparing between the reformate gas produced using SLP catalyst and pure hydrogen as feed for the fuel cell, the HT-PEMFC showed almost no difference in the voltage-current characteristic curve in the technically relevant operating points between 500 and 700 mV cell voltage. Furthermore, a pinch analysis indicated that the combination of a low-temperature MSR and HT-PEMFC presents an opportunity for heat-integration which could lead to increased efficiency.
CRIS-Team Scopus Importer:2025-10-16

Research progress on hydrogen production via methanol steam reforming: Catalysts, reactors, and mechanisms - Hu, Guangkai; Zhang, Xin; Yu, Bin; Huang, Tao; Liu, Mengjiao; Rehman, Muhammad; Li, Yongxiang; Jin, Fangwei; Yu, Hao; Haumann, Marco (International Journal of Hydrogen Energy, 2025)
Hydrogen (H2) has been considered as an ideal alternative energy carrier for addressing the energy crisis and environmental problems. Methanol steam reforming (MSR) reaction remains a candidate with unlimited potential for pursuing in-situ/distributed sustainable H2 production. In this review, the latest developments on catalysts, reactors, and mechanisms of MSR reaction are summarized. Specifically, coupling with the utilization of density functional theory (DFT) and machine learning (ML) techniques, the practicality and development trend of theoretical analysis in the MSR process is considered. Subsequently, different from the previous reviews, the progress on the commercial catalyst (Cu/ZnO/Al2O3) is addressed from the aspect of structural composition design, reaction parameters optimization, post-treatment process, heat sources and management, and integration with other energy systems. In addition, the elaborate design and modification of catalysts are thoroughly discussed, emphasizing the aspects of active species, supports, promoters, and preparation methods, as well as the effect of these aspects on the properties of the MSR reaction. Furthermore, various reactors, including packed-bed reactors, microreactors, membrane reactors, and self-Joule heating reactors, are presented according to the structure type, operation mode, and heat and mass transfer characteristics. Additionally, the reaction mechanism cycles of the Cu- and Pd-based catalysts are systematically proposed. Conclusively, a brief outlook of future MSR-related research is suggested. This review not only exhibits the overall research trajectory of state-of-the-art MSR-related catalysts, reactors, and mechanisms in a well-organized and attractive manner but also provides profound insights and guidance for their future study and development.
CRIS-Team Scopus Importer:2025-11-21
Keywords: Cu/ZnO/Al; Hydrogen production; methanol steam reforming; Reaction mechanism cycles; Self-Joule heating reactors